Smart city solutions in regard to urbanization processes - Brdulak, Halina (Logistics and sustainable transport, 2015)
The aim of this paper is to show the spectrum of problems associated with the growing importance of cities in the context of rapidly occurring processes of urbanization. Therefore the following issues are included: the concept of smart cities, which are a combination of the intelligent use of information systems allowing for active management of the various areas of urban activity with the potential of institutions, companies and the active involvement and creative people; transport problems and the use of new technologies. Particular attention will be given to both, the issue of transport congestion as the strongest factor affecting the quality of life of residents and to the role of social capital in the creation of sustainable development. To exemplify the result of the cooperation between southern Polish communities there will be presented a case of the introducing process of the Silesian Card of Public Services with a wide range of its functionality.
Keywords: city development; city logistics; logistika mest; pametna mesta; razvoj mest; smart cities; sustainable development; trajnostni razvoj; urbanizacija; urbanization